2007
DOI: 10.1111/j.1745-7254.2007.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gestrinone on uterine leiomyoma and expression of c-Src in a guinea pig model

Abstract: Aim: To investigate the effect of gestrinone on uterine leiomyomas and the expression of c-Src, estradiol receptors (ER), and progesterone receptors (PR) in a guinea pig model. Methods: After being oophorectomized, the guinea pigs were allocated into random groups. The model group was treated with estradiol benzoate (E 2 ) for 16 weeks. In the gestrinone-treated groups, the animals were treated with E 2 for 6 weeks in advance, and then in combination with gestrinone for 10 weeks. Histological examination was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Histologically, proliferative features were demonstrated, similar to the morphology observed in guinea pigs (Zhu et al, 2007). After treatment with Rh2, the relative uterine weight decreased and body weight increased in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Histologically, proliferative features were demonstrated, similar to the morphology observed in guinea pigs (Zhu et al, 2007). After treatment with Rh2, the relative uterine weight decreased and body weight increased in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 58%
“…Similar to gestrinone and gossypol, the mechanism of action of Rh2 involves regulating the activities of ERα/c-Src/p38 MAPK. First, we established an animal model of ULs by injecting oophorectomized rats subcutaneously with E2 and P4 (Fujii et al, 1981;Zhu et al, 2007). We did not utilize Eker rats because Eker rat tumours are dependent on E2 but not P4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression and aberrant activation of c-Src have been found in a variety of epithelial and non-epithelial cancers [11,12] . We demonstrated that c-Src was also over-expressed in a guinea pig model of uterine leiomyoma induced by estradiol [13] . This evidence suggests that Src may be involved in the development of leiomyoma.…”
Section: Introductionmentioning
confidence: 96%